AVV over ETCS (Current Problems in Rail Vehicles, 2025)
The paper deals with the issue of transition from the national ATO system AVV to a fully interoperable ERTMS/ATO with the intermediate step AVV over ETCS, analyzes changes to vehicles, track "hardware" and infrastructure data description. It describes individual solutions for retrofit installations according to the supplier of the ETCS mobile part and considers the future of track information points.
Keywords: automatic train operation; AVV; ERTMS/ATO; MIB